Design of a novel CNTs-based monopole for miniaturized wireless communication systems - Peng, Xinyu (Nanyang Technological University, 2024)
This paper explores the design and simulation of innovative Carbon Nanotube (CNT)- based monopole antennas for miniaturized wireless communication systems, aiming to tackle the challenges of antenna miniaturization while enhancing performance within the high-frequency radiation spectrum. With the promising potential candidate materials – Vertically Aligned Carbon Nanotubes (VACNTs) being focused on, three key models will be presented in this study: a bulk equivalent bundle SWCNT monopole model concept, a coplanar waveguide-fed (CPW-fed) monopole antenna with an integrated wire medium structure for gain enhancement, and coaxial probe-fed monopole antenna arrays. Each model utilizes the unique electrical and mechanical properties of CNTs to achieve significant miniaturization compared to metallic antennas and meaningful explorations in radiation efficiency, directionality, and gain, exhibiting the potential applications in advanced wireless systems. The simulated results acquired from HFSS software have demonstrated the advantages of incorporating CNTs into antenna designs and a promising direction for future research in the field of wireless communications have been offered – Phase Antenna. This study can be regarded as the pilot research for the development of high-performance, miniaturized antennas that can meet the evolving demands of modern and future wireless networks in high radiation frequency.